Language integration of forced and economic migrants in Croatia, Jezična integracija prisilnih i ekonomskih migranata u Hrvatskoj - Ranka Đurđević; Jelena Cvitanušić; Sanja Fulgosi (Slovenščina 2.0: Empirične, aplikativne in interdisciplinarne raziskave, 2024)
This paper presents an overview of the language integration of new migrants (refugees and asylum seekers, additionally foreign workers) in Croatia. Special emphasis is placed on the current practice and future needs for teaching and testing Croatian as L2 regarding forced migration (refugees, asylum seekers and asylees) and the increasing economic migration, which Croatia is currently experiencing. The roles of state and educational institutions, as well as of the policy and legal framework of (language) integration of vulnerable groups of learners is described.